EFISIENSI PENGGUNAAN SISTEM AERASI – MULTI SOIL LAYERING (MSL) DALAM PENGOLAHAN LIMBAH LAUNDRY - Khoiriyah, Aldina Fitri; Rahman, Nanik Astuti (Teknik Kimia ITN Malang, 2024)
The increasing number of migrants in Pandaan District, Pasuruan, has led to a rise in the number of laundry services. However, laundry operations have negative environmental impacts due to the disposal of untreated laundry wastewater into water bodies. Based on initial characteristic tests, the TSS, BOD, and COD in laundry wastewater were found to exceed the quality standards set by the East Java Governor Regulation No. 72 of 2013. This study aims to examine the effects of aeration time and variations in the dimensions of the Soil Mixture Block (SMB) on the treatment of laundry wastewater using the Aeration – Multi Soil Layering (MSL) system, regarding the reduction of TSS, BOD, and COD levels. The aeration times used were 0, 30, 60, 90, and 120 minutes, while the SMB dimensions varied as follows: (4×20×4) cm, (4×20×8) cm, and (4×20×12) cm. The results demonstrated that the Aeration-MSL system was effective in reducing the concentrations of TSS, BOD, and COD. The optimal variation was found with an aeration time of 120 minutes and an SMB dimension of (4×20×12) cm, which resulted in a reduction of TSS by 78%, BOD by 93.79%, and COD by 88%.